PELAKSANAAN PELATIHAN PRAMUBAKTI DALAM MENINGKATKAN KEMAMPUAN PEMELIHARAAN BARANG MILIK NEGARA DI UNIVERSITAS SINGAPERBANGSA KARAWANG - Rifa'i, Irpan; Meilya, Ika Rizqi; Syahid, Ahmad (IKIP Siliwangi, 2025)
Abstract Based on the existing conditions in preliminary research, the purpose of this study is to analyze and review the implementation of service attendant training in the maintenance of State Property at Singaperbangsa University Karawang and explain and describe the results of the implementation of the training. This research is optimally pursued in researching the subject matter based on data, institutional facts, recognition, and evaluation relying on case studies. The research uses qualitative research methods (natural setting) through a case study method approach, especially efforts to reveal the implementation of service guide training to improve BMN maintenance carried out by tracing and seeking information from training organizers and training participants. Sampling was carried out by snowball sampling involving 4 informants, consisting of 2 training managers and 2 training participants. The results of this study confirm that training can have a positive and significant impact. Training provides service personnel with the knowledge and skills necessary for BMN maintenance. Includes an understanding of the correct methods, and tools used while working (best practice). Stewards who attended the training also became more aware of the importance of the role in maintaining BMN. Pramubakti can identify risks and actions to be taken to avoid damage to BMN. The implementation of training for Pramubakti is now expected to be sustainable in mastering other understandings that continue to develop by the times.